Biotechnology sewage treatment (Eurasian Journal of Ecology, 2016)
The sewage of Mubareksky gas-processing plant cleared in biological ponds with use of microorganisms and the highest water plants, is optimum way of a solution of the problem of destruction of various pollutants. This technologyis characterized by profitability, high efficiency and ecological safety.
Keywords: biotechnology; sewage; bacteria-destructors; higher aquatic vegetation